CMR Native T1 Mapping Allows Differentiation of Reversible Versus Irreversible Myocardial Damage in ST-segment–Elevation Myocardial Infarction: An OxAMI Study (Oxford Acute Myocardial Infarction). (August 2017) - Liu, Dan; Borlotti, Alessandra; Viliani, Dafne; Jerosch-Herold, Michael; Alkhalil, Mohammad; De Maria, Giovanni Luigi; Fahrni, Gregor; Dawkins, Sam; Wijesurendra, Rohan; Francis, Jane; Ferreira, Vanessa; Piechnik, Stefan; et al.
Abstract : Background—: CMR T1 mapping is a quantitative imaging technique allowing the assessment of myocardial injury early after ST-segment–elevation myocardial infarction. We sought to investigate the ability of acute native T1 mapping to differentiate reversible and irreversible myocardial injury and its predictive value for left ventricular remodeling. Methods and Results—: Sixty ST-segment–elevation myocardial infarction patients underwent acute and 6-month 3T CMR, including cine, T2-weighted (T2W) imaging, native shortened modified look-locker inversion recovery T1 mapping, rest first pass perfusion, and late gadolinium enhancement. T1 cutoff values for oedematous versus necrotic myocardium were identified as 1251 ms and 1400 ms, respectively, with prediction accuracy of 96.7% (95% confidence interval, 82.8% to 99.9%). Using the proposed threshold of 1400 ms, the volume of irreversibly damaged tissue was in good agreement with the 6-month late gadolinium enhancement volume ( r =0.99) and correlated strongly with the log area under the curve troponin ( r =0.80) and strongly with 6-month ejection fraction ( r =−0.73). Acute T1 values were a strong predictor of 6-month wall thickening compared with late gadolinium enhancement. Conclusions—: Acute native shortened modified look-locker inversion recovery T1 mapping differentiates reversible and irreversible myocardial injury, and it is a strong predictor of left ventricular remodeling in ST-segment–elevation myocardial infarction. A single CMR acquisition of native T1 mapping could potentially represent a fast, safe, and accurate method for early stratification of acute patients in need of more aggressive treatment. Further confirmatory studies will be needed. Abstract : Supplemental Digital Content is available in the text.